(untitled) (Malaysian Journal of Learning and Instruction, 2022)
Purpose – The main objective of this study was to identify the influence of principal instructional leadership on teacher organizational commitment in junior high schools in Surakarta. This issue arises because there are discrepancies in the findings of previous studies as well as the lack of studies in Indonesia. Accordingly, no definitive conclusions can be drawn in relation to this issue which is still pending. Methodology – This study was conducted by applying a quantitative approach and cross-sectional survey design. A total of 264 teachers participated in this study. They were selected using a stratified random technique. Two standardized questionnaires namely the Principal Instructional Management Rating Scale (PIMRS) developed by Hallinger and Murphy (1985) and the Organizational Commitment Questionnaire (OCQ) developed by Allen and Meyer (1990) were used to measure principal instructional leadership and teacher commitment to their respective organizations. To analyze the data, SPSS version 26 was used to analyze the descriptive data, while SmartPLS 3.0 was used to analyze the measurement model and hypothesis testing. Findings – Descriptive statistics showed that the mean score of principal instructional leadership was 3.7 and teacher organizational commitment was 3.3. Both of these mean scores indicated that the level of principal instructional leadership and teacher organizational commitment were at moderate levels. In the assessment of the measurement model, the questionnaires used in the study had acceptable convergent and discriminant validity. Meanwhile, in hypothesis testing, this study found that principal instructional leadership had a moderate influence (β= 0.397) on teacher organizational commitment. Significance – The findings of this study have contributed to the development of knowledge in the field of instructional leadership and organizational commitment in the context of education in Indonesia. This study suggests that if teachers’ commitment to the school/ organization is to be enhanced, school principals should practice extensive instructional leadership.